1, 4, 2-Diazaborole-type heterocycle from 2H-azirine-2-carboxylate and [(alkylamino)methyl]trifluoroborate. (20th July 2022) - Oba, Toru; Takahashi, Hiroto; Roppongi, Makoto; Miyata, Kota
Graphical abstract: Highlights: Addition of acyclic amine-trifluoroborate to 2 H -azirine was examined. 1, 4, 2-Diazaborole-type heterocycle was obtained. The reaction included unusual cleavage of the azirine C2–C3 bond. The finding will contribute in developing boron-containing peptidomimetics. Abstract: A 1, 4, 2-diazaborole-type heterocycle was obtained via addition of [(alkylamino)methyl]-trifluoroborate to 2 H -azirine-2-carboxylate. The molecular structure of the product was confirmed by X-ray crystallography. The reaction proceeded at ambient temperature without metal catalysts and induced cleavage of the azirine C2–C3 bond without photoirradiation. This product can be regarded as a boron-containing peptidomimetic molecule that has potential applications in medicinal and synthetic chemistry.